The development of concepts of the resilience phenomenon in foreign psychology - Verbitskaya, Olga N.; Fofanova, Galina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article presents the results of an analysis of international scientific research on psychological resilience. Four waves of research on this phenomenon are identified. The first wave was phenomenological in nature, with scientists seeking to identify the specific characteristics of resilient individuals. In the second wave of research, scientists focused on the influence of environmental factors on individual resilience. The third wave was a period of intervention studies and experimental interventions aimed at exploring ways to enhance resilience. During the fourth wave, psychologists examined resilience as a multi-layered phenomenon, the study of which involves interaction between psychology and other fields of scientific knowledge.
Keywords: resilience; resilience concepts; four waves of resilience research